Multielectrode phased radiofrequency ablation compared with point-by-point ablation for pulmonary vein isolation – outcomes in 539 patients - Spitzer SG; Karolyi L; Weinmann T; Scharfe F; Rämmler C; Otto T; Jung F; Kadalie CT (Research Reports in Clinical Cardiology, 2014)
Stefan G Spitzer,1 Laszlo Karolyi,1 Thomas Weinmann,1 Frank Scharfe,1 Carola Rämmler,1 Tobias Otto,1 Friedrich Jung,2 Clemens T Kadalie11Praxisklinik Herz und Gefäße, Akademische Lehrpraxisklinik der TU Dresden, Dresden, Germany; 2Saarland University, Homburg, Saar, GermanyPurpose: To provide data on acute and long-term outcomes from pulmonary vein isolation with the pulmonary vein ablation catheter (PVAC) in patients with paroxysmal or persistent atrial fibrillation (AF).Methods: This was a single-center, retrospective, nonrandomized, case control study. Patients with documented symptomatic paroxysmal or persistent AF were treated with PVAC or with point-by-point radiofrequency ablation guided by the NavX™ mapping system. All follow-up visits were conducted in our center at 1 month, 3 months, and 6 months, and then at 6-month intervals. Electrocardiography and 24-hour Holter monitoring were performed at each follow-up visit. The endpoints included procedure times, acute and 24-month outcomes, and complications.Results: Of the 539 patients that were enrolled consecutively, 388 were ablated using PVAC and 151 using radiofrequency ablation. More patients with paroxysmal AF were treated with PVAC than with radiofrequency ablation. Acute success rates were >99% with both methods. Procedure duration and fluoroscopy times were significantly (P<0.001) shorter with PVAC than with point-by-point ablation. Rates of freedom from AF at all follow-up times available (up to 24 months) were significantly higher after PVAC ablation than with radiofrequency ablation (64.2% versus 48.2% at 24 months). With both ablation strategies, the rates of freedom from AF were higher in patients with paroxysmal AF than for persistent AF. Two posterior cerebral infarcts occurred in the PVAC group within 2 days of the procedure. No phrenic nerve injuries and no esophageal injuries were recorded. Data on embolic lesions were not collected.Conclusion: PVAC ablation achieved higher 24-month rates of AF-free survival than conventional radiofrequency ablation. Procedure and fluoroscopy times were shorter with PVAC, although the differences between groups may have influenced the results.Keywords: arrhythmia, atrial fibrillation, catheter ablation, pulmonary vein isolation, long-term follow-up, safety